Occurrence of veterinary pharmaceuticals in golden eagle nestlings: Unnoticed scavenging on livestock carcasses and other potential exposure routes - Blanco, Guillermo; Junza, Alexandra; Barrón, Dolores (Science of The Total Environment, 2017)
Wildlife exposure to pharmaceuticals can occur through contaminated water, and through the excreta and carcasses of medicated livestock, with potential for bioaccumulation and transfer through food webs. We evaluated whether nestling exposure to pharmaceuticals can occur from food delivered to nests in the golden eagle (Aquila chrysaetos), a top predator and facultative scavenger. Despite the fact that diet analysis suggests an apparently low dependence on livestock carcasses reduced to two piglets remains (1.5% of food remains, n = 134), a high proportion of nestlings (71%, n = 7) showed fluoroquinolone residues in plasma, mostly enrofloxacin, which is exclusively used in veterinary treatments. The occurrence and concentration (54.5 ± 6.6 μg·L) of fluoroquinolones in plasma was similar to those found in the nestlings of three vulture species largely dependent on livestock carcasses obtained at supplementary feeding stations, which are managed for the conservation of their populations. Although the number of analysed eaglets is comparatively small, the fact that enrofloxacin was found in all nests sampled in three breeding seasons suggest an exposure to the drugs similar to that of vultures. An underestimation of the role of carrion, especially from small piglets whose consumption may have gone unnoticed, and the predation of semi-domestic prey and generalist prey exploiting carcasses of medicated livestock, can contribute to explaining the unexpectedly high occurrence of these drugs in eaglets. Funds were provided by the projects CGL2009-12753-C02-01/BOS and CGL2010-15726 of Spanish Ministerio of Economía y Competitividad. Peer Reviewed